SOLID LIPID NANOPARTICLES (SLNs) AS NANO DRUG DELIVERY CARRIERS: PREPARATION, CHARACTERIZATION AND APPLICATION - QUSHAWY, MONA; NASR, ALI (International Journal of Applied Pharmaceutics, 2020)
Over the last few years, there has been a significant consideration of solid lipid nanoparticles (SLNs) as an alternative method to other colloidal dispersion methods for drug delivery. Special consideration has been given to the use of SLNs as a drug carrier in recent years. SLNs are aqueous dispersions in which the colloidal particles consist of solid lipids that are biodegradable. As a result of their physical stability, the protection of the entrapped drug from decomposition, the provision of controlled drug release, and the exceptional acceptability, SLNs have several advantages over other drug carriers. This article focuses on the techniques of SLNs preparation and characterization, the effect of formulation variables on SLNs properties, the routes of administration, and the pharmaceutical applications. The data used for this review was collected by searching on Google Scholar and PubMed using the following keywords during the period from 2010 to date.